Anti‐platelet antibody immunoassays in childhood immune thrombocytopenia: a systematic review - Schmidt, David E. (Vox Sang, 2020)
BACKGROUND: In adult immune thrombocytopenia (ITP), an acquired autoimmune bleeding disorder, anti‐platelet autoantibody testing may be useful as a rule‐in test. Childhood ITP has different disease characteristics, and the diagnostic and prognostic value of anti‐platelet antibody testing remains uncertain. OBJECTIVE: To systematically review the diagnostic accuracy of anti‐platelet autoantibody testing in childhood ITP. METHODS: PubMed and EMBASE were searched for studies evaluating immunoassays in childhood ITP. Study quality was assessed (QUADAS2), and evidence was synthesized descriptively. RESULTS: In total, 40 studies (1606 patients) were identified. Nine studies reported sufficient data to determine diagnostic accuracy measures. Anti‐platelet IgG antibody testing showed a moderate sensitivity (0·36–0·80 platelet‐associated IgG [direct test]; 0·19–0·39 circulating IgG [indirect test]). In studies that reported control data, including patients with non‐immune thrombocytopenia, specificity was very good (0·80–1·00). Glycoprotein‐specific immunoassays showed comparable sensitivity (three studies) and predominantly identified IgG anti‐GP IIb/IIIa antibodies, with few IgG anti‐GP Ib/IX antibodies. Anti‐platelet IgM antibodies were identified in a substantial proportion of children (sensitivity 0·62–0·64 for direct and indirect tests). CONCLUSION: The diagnostic evaluation of IgG and IgM anti‐platelet antibodies may be useful as a rule‐in test for ITP. In children with insufficient platelets for a direct test, indirect tests may be performed instead. A negative test does not rule out the diagnosis of ITP. Future studies should evaluate the value of anti‐platelet antibody tests in thrombocytopenic children with suspected ITP.